2021
DOI: 10.5653/cerm.2020.03937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different intensities of exercise on folliculogenesis in mice: Which is better?

Abstract: Objective: Exercise is a risk factor for infertility in women. However, research on the effects of different intensities of exercise on folliculogenesis has not yielded clear results. This study was conducted to analyze the effects of differences in the intensity of exercise on folliculogenesis in mice. Methods: Nineteen female BALB/c mice (age, 3–4 months; weight, 13–25 g) were randomly divided into four groups: control, mild exercise, moderate exercise, and high-intensity exercise. The mice in the exercise g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
1
1
Order By: Relevance
“…Regular exercise is an important component of supporting long-term weight loss. Changes in body weight occur as a result of compensatory mechanisms by the body [22]. Different results were shown with this study, a study on 162 women between the ages of 19 and 42 and found that moderate-intensity physical activity was associated with higher level of anti-Müllerian hormones and FSH.…”
Section: Discussioncontrasting
confidence: 77%
“…Regular exercise is an important component of supporting long-term weight loss. Changes in body weight occur as a result of compensatory mechanisms by the body [22]. Different results were shown with this study, a study on 162 women between the ages of 19 and 42 and found that moderate-intensity physical activity was associated with higher level of anti-Müllerian hormones and FSH.…”
Section: Discussioncontrasting
confidence: 77%
“…Changes in physical activity have a positive effect on sexual health in the form of: more frequent sexual intercourse, better vaginal lubrication, and overall sexual function 5 years later (Wekker et al, 2018). Exercise with intensity moderate indicates a tendency for a higher number of follicles (Rahayu et al, 2021). The study also shows that moderate-intensity exercise has a positive effect on ovarian reserve due to the number of apoptotic follicles in the group undergoing less sports training.…”
Section: Introductionmentioning
confidence: 56%
“…Differences in intensity between exercise groups using weights placed on the mice's tails. Swimming exercise was carried out with a load of 3% of body weight for low-intensity exercise (Rahayu et al, 2021), 6% of body weight for moderateintensity exercise (Antoni et al, 2022), and 9% of body weight for high-intensity exercise (Rahayu et al, 2021). The water temperature was maintained between 30-32°C (Evangelista et al, 2003).…”
Section: Protocol Of Exercisementioning
confidence: 99%